Colligational Problems Faced by English Majors - Yusra Mohammed Salman (QALAAI ZANIST JOURNAL, 2022)
The main concern of this paper is to explore and diagnose first year English Majors’ use of colligations (grammatical collocations), and the problems they face in this respect. The research aims at making a clear-cut distinction between two distinctive types that characterize the combinatory nature of English language; collocation and colligation. The focus of this research paper is on the types of colligations and the contexts in which they occur, and the suggested method of treatment which depends mainly on awareness-raising strategies. The students’ actual knowledge and performance of certain colligations were checked via a test designed for that purpose. The process of test analysis revealed the size and nature of the problems the first year English majors faced, and suitable solutions had been suggested to cope with those problems.